Preservation and place : historic preservation by and of LGBTQ communities in the United States - Crawford-Lackey, Katherine; Springate, Megan E. (Preservation and place, 2019)
"Significant historic and archaeological sites affiliated with two-spirit, lesbian, gay, bisexual, transgender, and queer history in the United States are examined in this unique volume. The importance of the preservation process in documenting and interpreting the lives and experiences of queer Americans is emphasized. The book features chapters on archaeology and interpretation, as well as several case studies focusing on queer preservation projects. The accessible text and associated activities create an interactive and collaborative process that encourages readers to apply the material in a hands-on setting"--